Halal logistics: manipulation in packaging, labeling and retailing issues - Ishak, Fahrul Irfan; Abdullah, Mohd Amri; Awang, Mohd Daud; Ab Rahman, Suhaimi (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
This paper explains the issues have been arisen in Malaysia in Halal Logistics. Halal is about global industry that requires connections and logistics of goods and services especially for more than 1.6 billion Muslim people around the globe. However, some issues have been discovered in Halal Logistics that have to be given attention such as manipulation in packaging, labeling by manufacturers or distributors or and weaknesses of retailer in managing Halal products. This paper presents 152 findings of products that labelled with Halal logo in the supermarket in Pasir Gudang area. The products covered twenty types of food, beverage and cosmetic, certified halal by various certifying bodies internationally. These issues have taken place due to several factors of regulators, retailers and consumers. Even though many actions have been taken by retailers to fulfill halal requirement, the awareness of halal retailers should be increased to ensure the benefit to consumers will be given priority.